A identidade do sujeito constitucional e o direito fundamental à licença-paternidade: da paternidade tradicional às paternidades constitucionais - Stanley Souza Marques (2016)
Proliferate indicators that ongoing changes (not only) in brazilian society are related less to sexual redivision of labor and time than the diversity and plasticity of families and the labor market. If motherhood myth partly explains the time and types of different involvement between men and women in the care of children and housework, it does not exhaust the diagnosis particularly unfavorable to women. Domestic duties's democratic redivision and child care also come up against naturalized conceptions of masculinity and fatherhood. That is why after reconstructed socio-historical movements fragments that gave form and content to modern models of good motherhood, not without tensions and transgressions, this dissertation seeks to further demystify design and deconstruction of substantive gender appearance, also shared by studies on men and masculinities. Not only demand increase it as you drag it to the ground of the identity of the constitutional subject, more precisely from the fundamental right to paternity leave, here focused as integral part of the challenges posed by the Constituent Project 1988. This is because the constitutional reconstruction and democratic gender order seem to go by paternity leave, though not reduce the extension of this fundamental right